Properties and Reactivity of Conformationally Constrained Bicyclic Diarylprolinol Silyl Ethers as Organocatalysts1. Issue 27 (19th August 2014) - Lombardo, Marco; Cerisoli, Lucia; Manoni, Elisabetta; Montroni, Elisa; Quintavalla, Arianna; Trombini, Claudio
Abstract: Bicyclic silyl ether derivatives1, which are derived from simple chemical manipulations of trans ‐4‐L ‐hydroxyproline, were recently proposed, by us, as conformationally constrained analogues of Jørgensen–Hayashi's catalysts2 . Despite the structural similarities, 1 displays remarkable performance in iminium chemistry with respect to2, but much lower reactivity in enamine chemistry. The peculiar structural features of1 confer a pattern of reactivity between Jørgensen–Hayashi's catalysts and MacMillan's imidazolidinones. Abstract : Bicyclic silyl ether derivative1a, which is easily prepared from trans ‐4‐L ‐hydroxyproline, is much more stable toward protodesilylation than Jørgensen–Hayashi's catalyst2a . Despite their structural analogy, 1a behaves as a very efficient catalyst in iminium chemistry, but is much less active than2a in the enamine activation mode. Here, 1a exhibits a higher or equivalent level of stereocontrol.